Soda-aluminum-silica glass, anti-glare glass, and preparation method and application thereof

By adjusting the oxide composition and surface treatment process of sodium aluminum silicon glass, high transmittance and low haze anti-glare glass is prepared, which solves the problem of traditional glass glare and meets the optical performance needs of electronic consumer goods and large display screens.

CN116395956BActive Publication Date: 2025-04-18QINGYUAN CSG NEW ENERGY SAVING MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310098027.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-10
Publication Date
2025-04-18
Estimated Expiration
2043-02-10

AI Technical Summary

Technical Problem

Traditional glass is prone to glare on high-gloss surfaces, causing eye irritation, and has safety risks in industrial production and transportation. The existing anti-glare glass has low transmittance and cannot meet the optical performance needs of electronic consumer goods and large display screens.

Method used

By adjusting the oxide composition ratio of sodium-aluminum silicon glass, combined with pre-etching, frosting and pickling treatment, anti-glare glass with high transmittance, extremely poor gloss and small haze were prepared. The surface treatment was carried out with a specific composition of frosting and acid liquid to control the erosion coefficient and frosting time to ensure the uniformity of the glass surface.

Benefits of technology

While maintaining high transmittance, it significantly improves anti-glare performance, improves gloss and reduces haze, meeting the optical performance needs of consumer electronics and large displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a sodium aluminum silicate glass, which includes the following components by mass percentage: 58% to 70% SiO2, 8% to 15% Al2O3, 13% to 18% Na2O, 2.5% to 5.5% K2O, 2% to 5.5% MgO, 0% to 3% CaO, 0% to 1.5% ZrO2, and 0% to 1.5% B2O3; wherein, the mass percentage of the components is used for calculation, and the following formula is satisfied: 66%≤(SiO2+Al2O3)‑(CaO+MgO)≤75%, 85%≤(Na2O+K2O)×(SiO2 / Al2O3‑CaO / MgO)≤115%. By finely adjusting the ratio between the oxide components, the sodium aluminum silicate glass has a reasonable distribution gradient of corrosion-resistant components and susceptible components, which is conducive to forming anti-glare glass with good optical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of anti-glare glass, and in particular to a sodium aluminum silicate glass, anti-glare glass, and a preparation method and application thereof. Background Art

[0002] With the popularity of electronic consumer products and large display screen applications, the demand for large-screen touch and multi-screen interaction has put forward higher requirements on the optical performance of display modules. The glass used in traditional technology as an OLED cover has good light transmittance, but its high-gloss surface is prone to glare, which irritates the user's eyes and may even bring safety risks in the fields of industrial production and transportation. Summary of the invention

[0003] Based on this, one of the purposes of the present application includes providing a sodium aluminum silicate glass, which can obtain anti-glare glass with high light transmittance and glossiness, extremely poor glossiness and low haze after frosting treatment by adjusting the ratio between the various oxide components. In addition, the present application also provides an anti-glare glass, a preparation method and an application.

[0004] In a first aspect of the present application, a sodium aluminum silicate glass is provided, characterized in that, in terms of mass percentage, the raw materials for preparation include the following components: 58% to 70% SiO2, 8% to 15% Al2O3, 13% to 18% Na2O, 2.5% to 5.5% K2O, 2% to 5.5% MgO, 0% to 3% CaO, 0% to 1.5% ZrO2, and 0% to 1.5% B2O3;

[0005] Among them, the calculation is based on the mass percentage of the components and satisfies the following formula: 66%≤(SiO2+Al2O3)-(CaO+MgO)≤75%, 85%≤(Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO)≤115%.

[0006] In some embodiments, the erosion coefficient of the sodium aluminum silicate glass, calculated based on the mass percentage of the components, is γ=(1.5×SiO2+CaO) / ln(Al2O3×100), and the range of γ is 0.3 to 0.6.

[0007] In some embodiments, the sodium aluminum silicate glass, calculated by weight percentage of the components, satisfies one or more of the following characteristics (1) to (3):

[0008] (1)68.2%≤(SiO2+Al2O3)-(CaO+MgO)≤74%;

[0009] (2)89.8%≤(Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO)≤112.4%;

[0010] (3) The erosion coefficient γ ranges from 0.35 to 0.51.

[0011] A second aspect of the present application provides a method for preparing anti-glare glass, comprising the following steps:

[0012] The sodium aluminum silicate glass described in the first aspect is placed in a first acid solution containing hydrofluoric acid as a glass original sheet for pre-etching, and then washed and dried after the pre-etching;

[0013] The crude product after pre-etching treatment is placed in a frosting solution for frosting treatment for 60s to 120s;

[0014] The frosted crude product is placed in an acid solution without hydrofluoric acid for pickling, and then post-polished in a second acid solution containing hydrofluoric acid, washed and dried.

[0015] In some embodiments, the preparation method, in parts by weight, the frosting liquid contains 6-10 parts of ammonium bifluoride, 4-6 parts of potassium fluoride, 4-6 parts of ammonium sulfate, 5-7 parts of potassium sulfate, 2-5 parts of hydrochloric acid, 1-2 parts of sulfuric acid, and 10-15 parts of water.

[0016] In some embodiments, the preparation method satisfies one or more of conditions (1) to (3):

[0017] (1) The first acid solution containing hydrofluoric acid is prepared by 40 to 60 parts of 15 g / mL hydrofluoric acid and 40 to 60 parts of 6 g / mL sulfuric acid, calculated by weight;

[0018] (2) The acid solution not containing hydrofluoric acid is prepared by 40 to 60 parts by weight of 16 g / mL sulfuric acid and 40 to 60 parts by weight of 5 g / mL hydrochloric acid;

[0019] (3) The second acid solution containing hydrofluoric acid is prepared by 40 to 60 parts by weight of 15 g / mL hydrofluoric acid and 40 to 60 parts by weight of 6 g / mL sulfuric acid;

[0020] (4) The pre-etching treatment time is 5 to 20 seconds;

[0021] (5) The pickling time is 2 to 7 minutes;

[0022] (6) The time of the post-throwing treatment is 7 to 14 minutes.

[0023] In some embodiments, the preparation method, calculated by substituting the mass percentage of the components, the erosion coefficient γ = (1.5 × SiO2 + CaO) / ln (Al2O3 × 100), also satisfies one of the following conditions (1) to (3):

[0024] (1) When the erosion coefficient γ is 0.356-0.39, the frosting treatment time is 120s±5s;

[0025] (2) When the erosion coefficient γ is 0.391 to 0.45, the frosting treatment time is 90s±4s;

[0026] (3) When the erosion coefficient γ is 0.451-0.519, the frosting treatment time is 60s±3s.

[0027] A third aspect of the present application provides an anti-glare glass prepared by the preparation method described in the second aspect.

[0028] A fourth aspect of the present application provides a glass-containing product, including a glass structure, wherein the glass structure is prepared using the anti-glare glass described in the third aspect.

[0029] The fifth aspect of the present application provides an application of the anti-glare glass described in the third aspect or the glass product described in the fourth aspect in the preparation of display screens and curtain walls.

[0030] The present application makes the surface of sodium aluminum silicate glass have appropriate surface tension by finely adjusting the ratio between each oxide composition, wherein the distribution gradient of corrosion-resistant components and corrosion-susceptible components is reasonable, and the thermodynamic barrier for fusion between each component of the glass is small, which is conducive to the preparation of anti-glare glass with good comprehensive performance of transmittance and anti-glare. When used to prepare anti-glare glass, a balance can be achieved between the ion escape velocity and crystal precipitation velocity on the glass surface through the pre-etching and etching steps, which can make the glass surface uniformly etched, which is conducive to improving the transmittance, reducing the thermodynamic barrier for fusion between the glass components, and forming anti-glare glass with good optical properties; the preparation method has a simple process, high efficiency, and low pollution of frosting liquid components; the anti-glare glass has high transmittance and low haze, and it also has excellent gloss and gloss extreme difference and surface roughness parameters. DETAILED DESCRIPTION

[0031] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0033] the term

[0034] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0035] Herein, "preferred", "better", "more preferred", and "suitable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of this application. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0036] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0037] In this application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions of the listed features.

[0038] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for broadly including quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0039] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0040] Soda-aluminosilicate glass: generally refers to silica glass whose main components are sodium oxide and aluminum oxide. The soda-aluminosilicate glass in this application also contains other oxides, such as first and second main group oxides such as potassium oxide, magnesium oxide, calcium oxide, as well as zirconium oxide, boron oxide and other components.

[0041] Frosting treatment: In this application, it refers to the process of treating glass with frosting liquid. During the frosting process, the components in the frosting liquid continuously react chemically on the surface of the glass, causing erosion and forming small pits on the surface of the glass.

[0042] Anti-glare glass: In this application, it refers to glass with a surface diffuse reflection effect to avoid glare from reflected light.

[0043] Transmittance: The ratio of transmitted light energy to reflected light energy when light is incident perpendicular to the glass surface.

[0044] Gloss: How close the glass surface is to a mirror.

[0045] Haze: When light is incident perpendicular to the glass surface, the ratio of the intensity of transmitted light that deviates from the incident light by more than 2.5 degrees to the intensity of incident light.

[0046] Surface roughness: The maximum distance of the raised or recessed part of the surface relative to the reference plane.

[0047] In traditional technology, anti-glare glass often sacrifices transmittance in pursuit of excellent anti-glare performance. Generally speaking, the transmittance is less than 80%, while the glossiness is less than 50% and the haze is greater than 20%. Although this anti-glare glass can avoid glare stimulation to the user's eyes, the transparency is not satisfactory. As the display effect requirements for personal electronic consumer products, commercial and industrial fields become higher and higher, this traditional low-transmittance anti-glare glass can no longer meet the application needs.

[0048] After extensive research, the present invention has found a sodium aluminum silicate glass, an anti-glare glass and a preparation method and application thereof, which can better overcome the above problems. The obtained anti-glare glass product can achieve good anti-glare performance while ensuring that the transmittance is not greatly reduced.

[0049] In a first aspect of the present application, a sodium aluminum silicate glass is provided, wherein the raw materials for preparing the glass include the following components in terms of mass percentage: 58% to 70% SiO2, 8% to 15% Al2O3, 13% to 18% Na2O, 2.5% to 5.5% K2O, 2% to 5.5% MgO, 0% to 3% CaO, 0% to 1.5% ZrO2, and 0% to 1.5% B2O3;

[0050] Among them, the calculation is based on the mass percentage of the components and satisfies the following formula: 66%≤(SiO2+Al2O3)-(CaO+MgO)≤75%, 85%≤(Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO)≤115%.

[0051] The present application achieves a suitable surface tension on the surface of sodium aluminum silicate glass by finely adjusting the ratio between the various oxide components, wherein the distribution gradient of the corrosion-resistant components and the corrosion-susceptible components is reasonable, and the thermodynamic barrier to fusion between the various components of the glass is small, which is conducive to the preparation of anti-glare glass with good comprehensive transmittance and anti-glare performance.

[0052] Silicon dioxide (SiO2) is the main component of the glass skeleton. The tetrahedral spatial network structure formed by it makes the glass have good strength. When the silicon dioxide content in the glass increases, its viscosity and melting point also increase. Silicon dioxide can be corroded by hydrofluoric acid, but cannot be corroded by other commonly used dilute acids such as dilute hydrochloric acid and dilute sulfuric acid. Controlling the silicon dioxide content in sodium aluminum silicate glass within a suitable range has an important influence on the strength, processing difficulty and corrosion resistance of the glass. If the silicon dioxide content in sodium aluminum silicate glass is higher than the appropriate range, not only may the viscosity and melting point of the glass be higher, but the proportion of other components with better corrosion resistance will also decrease, so the corrosion resistance of the glass (mainly refers to the property of withstanding hydrofluoric acid corrosion) will decrease; if the silicon dioxide content in sodium aluminum silicate glass is lower than the appropriate range, it may lead to a decrease in production efficiency due to the high content of corrosion-resistant components in the glass during the subsequent frosting process, and the strength and weather resistance of the glass will be poor.

[0053] In some embodiments, the sodium aluminum silicate glass includes 58% to 70% SiO2 by mass percentage, and can further be 59% to 70%, and further can be 60% to 70%, and can also be selected from one or two of the following mass percentages: 58%, 58.5%, 59%, 59.5%, 60%, 60.5%, 61%, 61.5%, 62%, 62.5%, 63%, 63.5%, 64%, 64.5%, 65%, 65.5%, 66%, 66.5%, 67%, 67.5%, 68%, 68.5%, 69%, 69.5% or 70%.

[0054] Alumina is one of the important components of sodium aluminum silicate glass. In the glass structure, it generally enters the glass structure network in the form of tetrahedrons, which complements the skeleton structure of silicon oxide. Alumina can also improve the strength of glass and its corrosion resistance to etching liquid. Controlling the silica content in sodium aluminum silicate glass within a suitable range is conducive to obtaining anti-glare glass with high corrosion efficiency, balanced anti-glare performance and light transmittance performance. If the aluminum oxide content in sodium aluminum silicate glass is higher than the appropriate range, the viscosity of the glass may be too high and difficult to clarify, the melting quality may be reduced, and the various properties of the glass may be affected. In addition, due to the strong corrosion resistance, the efficiency of frosting treatment is low; if the aluminum oxide content in sodium aluminum silicate glass is lower than the appropriate range, it may lead to insufficient corrosion resistance in the subsequent frosting process, the corrosion process is too fast and difficult to control, and it is easy to cause uneven corrosion, making it difficult to obtain good gloss and surface roughness.

[0055] In some embodiments, the sodium aluminum silicate glass includes 8% to 15% Al2O3 by mass percentage, and can further be 8% to 14%, and further can be 8% to 13%. It can also be selected from one or two of the following mass percentages: 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5% or 15%.

[0056] Sodium oxide and potassium oxide are both first-group metal oxides, also known as alkali metal oxides. Both sodium oxide and potassium oxide can improve the processing properties of glass; due to the different radii of the two alkali metal ions, there are differences in the rates of being corroded by acid, exchanging ions with the components in the frosting liquid, or precipitating crystals containing corresponding cations during the frosting process. Controlling the contents of sodium oxide and potassium oxide in sodium aluminum silicate glass within appropriate ranges is conducive to improving the processing properties of the glass and easily obtaining anti-glare glass with good optical properties after frosting. If the content of sodium oxide in sodium aluminum silicate glass is higher than the appropriate range, the corrosion resistance of the glass may deteriorate; and if its content in sodium aluminum silicate is lower than the appropriate range, on the one hand, the processing properties of the glass (such as melting temperature) may be poor, and on the other hand, the efficiency during the frosting process may decrease. The influence of the content of potassium oxide in sodium aluminum silicate is similar to that of sodium oxide. If its content in sodium aluminum silicate glass is high, it may cause poor melting of the glass; if its content in sodium aluminum silicate glass is low, it may cause poor melting of the glass.

[0057] In some embodiments, the sodium aluminum silicate glass includes 13% to 18% Na2O by mass percentage, and can also be selected from one or two of the following mass percentages: 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5% or 18%.

[0058] In some embodiments, the soda-aluminum-silica glass includes 2.5% to 5.5% K2O by mass percentage, and can also be selected from one or two of the following mass percentages: 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4% or 5.5%.

[0059] Both magnesium oxide and calcium oxide are metal oxides of the second main group, also known as alkaline earth metal oxides. Both magnesium oxide and calcium oxide can reduce the viscosity of glass at high temperatures, promote the melting and clarification of glass; because magnesium oxide and calcium oxide belong to the network exosomes, they can provide free oxygen, thereby cutting off the glass network, making the glass network structure sparse and more susceptible to erosion, so they can adjust the corrosion resistance of the glass. Controlling the magnesium oxide content in sodium aluminum silicate glass within a suitable range is conducive to obtaining sodium aluminum silicate glass with moderate corrosion resistance and high frosting efficiency. If the content of magnesium oxide in sodium aluminum silicate glass is higher than the suitable range, it may cause the composition of the glass of the present application to contain ZrO2, which is a crystal nucleating agent that is easy to form magnesium aluminum silicate microcrystalline glass, resulting in crystallization; if its content in sodium aluminum silicate glass is low, it may cause its enhancement effect on the Na2O-K2O mixed alkali effect to be reduced, thereby reducing corrosion resistance.

[0060] In some embodiments, the soda-aluminum-silica glass includes 2% to 5.5% MgO by mass percentage, and can also be selected from one or two intervals of the following mass percentages: 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4% or 5.5%.

[0061] Introducing calcium oxide into sodium aluminum silicate helps to further reduce the viscosity of glass at high temperatures and promote the melting and clarification of glass. Since calcium oxide reduces the density of the glass network and is easy to react with HF, introducing more calcium oxide may damage the corrosion resistance of the glass, so it is necessary to control the calcium oxide content in sodium aluminum silicate within an appropriate range.

[0062] In some embodiments, the sodium aluminum silicate glass includes 0% to 3% CaO in terms of mass percentage, and can also be selected from one or two intervals of the following mass percentages: 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3.0%.

[0063] Introducing zirconium oxide into sodium aluminum silicate can help further improve the weather resistance and corrosion resistance of glass. However, it may also increase the viscosity of the glass, resulting in poor uniformity and low quality of the glass during the preparation process. Therefore, it is necessary to control the zirconium oxide content in sodium aluminum silicate within an appropriate range.

[0064] In some embodiments, the sodium aluminum silicate glass includes 0% to 1.5% ZrO2 in terms of mass percentage, and can also be selected from one or two of the following mass percentage intervals: 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%.

[0065] Introducing boron oxide into sodium aluminum silicate helps to further reduce the viscosity of glass at high temperatures. However, when the content of boron oxide is high, it exists in the form of boron-oxygen triangles, which reduces the density of the glass network structure. Introducing more boron oxide may significantly reduce the corrosion resistance of the glass and affect the frosting process, so it is necessary to control the content of boron oxide in sodium aluminum silicate within an appropriate range.

[0066] In some embodiments, the sodium aluminum silicate glass includes 0% to 1.5% B2O by mass percentage, and can also be selected from one or two of the following mass percentages: 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%.

[0067] In some embodiments, the sodium aluminum silicate glass includes, by mass percentage, 59% to 70% SiO2, 8% to 14% Al2O3, 13% to 18% Na2O, 2.5% to 5.5% K2O, 2% to 5.5% MgO, 0% to 3% CaO, 0% to 1.5% ZrO2, and 0% to 1.5% B2O3.

[0068] In some embodiments, the sodium aluminum silicate glass includes, by mass percentage, 60% to 70% SiO2, 8% to 13% Al2O3, 13% to 18% Na2O, 2.5% to 5.5% K2O, 2% to 5.5% MgO, 0% to 3% CaO, 0% to 1.5% ZrO2, and 0% to 1.5% B2O3.

[0069] In the present application, the sodium aluminum silicate glass needs to be subjected to surface treatment including frosting treatment to obtain anti-glare glass. In the surface treatment process including frosting treatment, the acid solution and the acid in the frosting solution act on the glass surface, so that the components on the glass surface that are susceptible to corrosion are dissolved from the glass surface and escape into the frosting solution; at the same time, after the concentration of the ions dissolved from the glass and the ions in the frosting solution reaches the upper limit of the solubility, the corresponding ions form crystals with a specific composition and precipitate on the glass surface.

[0070] As the frosting process progresses, more and more insoluble substances accumulate into granular crystals firmly adhering to the surface, hindering further acid etching reactions, and then forming non-uniform erosion, resulting in an uneven transparent surface. The frosting liquid or frosting process may affect the unevenness of the frosting process. When the unevenness is large, it may have a negative impact on the optical properties.

[0071] The applicant has found that when the content of the components in the sodium aluminum silicate glass meets a specific relationship, it is conducive to obtaining anti-glare glass with good gloss. It is possible that the glass has an appropriate surface tension at this time, and the reaction products can be separated from the glass surface at an appropriate speed, which promotes the process to proceed faster; the process has a leveling effect, that is, when the glass surface state or the frosting agent is not sufficiently uniform, this step-by-step reaction mode makes the overall reaction speed and degree controlled at a relatively stable level, so that the gloss consistency of the anti-glare glass is better.

[0072] In some embodiments, the sodium aluminum silicate glass satisfies the following formula when the mass percentage of the components is substituted into the calculation: 66%≤(SiO2+Al2O3)-(CaO+MgO)≤75%, and further the numerical range can be 66.5%~74.5%, and further the range can be 68.2%~74%.

[0073] The applicant also found that when the content of the components in the sodium aluminum silicate glass meets a specific relationship, it is conducive to obtaining an anti-glare glass with a higher transmittance. It may be that during the frosting process of the glass that meets this formula, the thermodynamic barrier for the fusion of the pits generated on its surface is smaller, so the degree of fusion is greater, the pit depth becomes shallower, and the light-trapping structure can cause the light to be reflected twice or even multiple times, and the transmittance of the glass is increased.

[0074] In some embodiments, in the sodium aluminum silicate glass, the mass percentage of the components is used for calculation and satisfies the following formula: 85%≤(Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO)≤115%, and further the numerical range can be 88% to 114%, and further the range can be 89.8% to 112.4%.

[0075] After a large number of experiments, the applicant also found that fine-tuning some of the components in the sodium aluminum silicate glass is conducive to significantly improving the efficiency of the sodium aluminum silicate glass frosting treatment and obtaining anti-glare glass with good optical properties. In this application, the relationship between the components in the formula is defined as the erosion coefficient, that is, the erosion coefficient γ = (1.5SiO2 + CaO) / ln (Al2O3 × 100). If the value of the erosion coefficient is higher than the appropriate range, it may result in low erosion resistance, a faster erosion rate of the frosting liquid on the glass, and higher control requirements for the frosting process. It is difficult to obtain glass products with good gloss and surface roughness, and the anti-glare effect is poor; if the value of the erosion coefficient is lower than the appropriate range, it may result in low erosion resistance, a slower erosion rate of the frosting liquid on the glass, and low production efficiency.

[0076] In some embodiments, the erosion coefficient γ of the sodium aluminum silicate glass, according to mass percentage, ranges from 0.3 to 0.6, further can be 0.32 to 0.55, further can be 0.35 to 0.51, and can also be selected from one or two of the following values: 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55 or 0.56.

[0077] In some embodiments, the sodium aluminum silicate glass, calculated based on the mass percentage of the components, satisfies: 68.2%≤(SiO2+Al2O3)-(CaO+MgO)≤74%.

[0078] In some embodiments, the sodium aluminum silicate glass, calculated based on the mass percentage of the components, satisfies: 89.8%≤(Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO)≤112.4%.

[0079] In some embodiments, the sodium aluminum silicate glass, calculated based on the mass percentage of the components, satisfies the following conditions: the erosion coefficient γ is in the range of 0.35 to 0.51.

[0080] In some embodiments, the sodium aluminum silicate glass, calculated based on the mass percentage of the components, satisfies: 68.2%≤(SiO2+Al2O3)-(CaO+MgO)≤74%, 89.8%≤(Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO)≤112.4%, and the erosion coefficient γ ranges from 0.35 to 0.51.

[0081] In a second aspect of the present application, a method for preparing anti-glare glass is provided, which can prepare anti-glare glass.

[0082] In some embodiments, the method for preparing the anti-glare glass comprises the following steps:

[0083] S100: placing the sodium aluminum silicate glass described in the first aspect as a glass original sheet in a first acid solution containing hydrofluoric acid for pre-etching, and washing and drying after the pre-etching;

[0084] S200: placing the pre-etched crude product in a frosting solution for frosting for 60s to 120s;

[0085] S300: The frosted crude product is placed in an acid solution without hydrofluoric acid for pickling, and then post-polished in a second acid solution containing hydrofluoric acid, washed and dried.

[0086] In some embodiments, the method for preparing the anti-glare glass comprises the following steps:

[0087] S100: placing the sodium aluminum silicate glass described in the first aspect as a glass original sheet in a first acid solution containing hydrofluoric acid for a pre-etching treatment for an appropriate period of time, and washing and drying after the pre-etching treatment;

[0088] S200: placing the pre-etched crude product in a frosting solution for frosting for 60s to 120s;

[0089] S300: The frosted crude product is placed in an acid solution without hydrofluoric acid for pickling, and then post-treated with a second acid solution containing hydrofluoric acid for an appropriate period of time, washed and dried.

[0090] In some embodiments, the method for preparing the anti-glare glass comprises the following steps:

[0091] S100: placing the sodium aluminum silicate glass described in the first aspect as a glass original sheet in a first acid solution containing hydrofluoric acid (hydrofluoric acid and dilute sulfuric acid of appropriate concentration) for a suitable period of time for pre-etching, and washing and drying after the pre-etching;

[0092] S200: placing the pre-etched crude product in a frosting solution for frosting for 60s to 120s;

[0093] S300: The frosted crude product is placed in an acid solution without hydrofluoric acid (dilute hydrochloric acid and dilute sulfuric acid of appropriate concentration) for pickling, and then post-treated with a second acid solution containing hydrofluoric acid (hydrofluoric acid and dilute sulfuric acid of appropriate concentration) for an appropriate period of time, washed and dried.

[0094] In the present application, the glass original sheet is pre-etched with an acid solution containing hydrofluoric acid, and then the glass is frosted with a frosting solution, and then pickled with an acid solution without hydrofluoric acid and post-polished with an acid solution containing hydrofluoric acid, so as to prepare an anti-glare glass with good light transmittance, glossiness, glossiness extreme difference, haze and roughness. The process flow is simple and the processing efficiency is high. Through pre-etching and frosting treatment with a frosting solution, combined with a simple pickling and post-polishing process, an anti-glare glass product with excellent optical properties can be obtained without repeated frosting, and an anti-glare glass with high glossiness (for example, ≥75%) is obtained while maintaining high transparency (for example, ≥88%).

[0095] Controlling the thickness of the original glass sheet within an appropriate range will help to obtain anti-glare glass with better transparency. If the thickness of the original glass sheet is higher than the appropriate range, the light transmission path of the frosted glass may be longer when used in display screens, the proportion absorbed by the glass may increase, and the transmittance may be lower; if the thickness of the original glass sheet is lower than the appropriate range, the glass may be thinned more (relative value) during the frosting process, the thickness of the uncorroded part of the glass may be insufficient, and the mechanical properties of the anti-glare glass product may be greatly reduced.

[0096] In some embodiments, in the preparation method, the thickness of the glass sheet is 0.5-1.0 mm, further can be 0.6-0.9 mm, further can be 0.6-0.8 mm, and can also be selected from one or two of the following thickness intervals: 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm, 0.7 mm, 0.75 mm, 0.8 mm, 0.85 mm, 0.9 mm, 0.95 mm or 1.0 mm.

[0097] As mentioned above, the applicant also found that by finely adjusting the partial composition of the sodium aluminum silicate glass and substituting the mass percentage of the components into the calculation, the following formula is satisfied: Erosion coefficient γ = (1.5SiO2 + CaO) / ln (Al2O3 × 100), where γ is in the range of 0.3 to 0.6, which is beneficial to significantly improve the frosting treatment efficiency in the preparation of anti-glare glass and obtain anti-glare glass with better optical properties. The preferred range can further be 0.32 to 0.55, and the more preferred range is 0.35 to 0.51.

[0098] When the erosion coefficient γ is lower than the above-mentioned suitable range, the glass may have a stronger ability to withstand the erosion of effective components in the frosting liquid, such as hydrofluoric acid, during the frosting process, and the components in the glass dissolve and leave the glass surface at a slower speed, and the proportion of components escaping into the frosting liquid due to erosion in the same time is smaller, so that it takes a longer time (for example, more than 3 to 5 minutes) to obtain the required erosion depth, and the production efficiency is reduced; at the same time, during the extended erosion time, the crystal precipitates are continuously deposited on the surface of the glass that is less eroded, which may hinder the further interaction between the glass surface and the effective erosion components in the frosting liquid, thereby causing uneven deposition of precipitates, which is manifested as a large glossiness extreme difference ΔG of the glass product (for example, it may be greater than 10%). When the erosion coefficient γ is higher than the above-mentioned suitable range, the frosting liquid has a stronger ability to erode the glass, a higher erosion efficiency, a shorter window interval between frosted windows, a higher control requirement for the frosting process, and greater difficulty in quality control of anti-glare glass.

[0099] In some embodiments, in the preparation method, the frosting treatment time is 60s to 120s, and can also be selected from one or two of the following time intervals: 60s, 65s, 70s, 75s, 80s, 85s, 90s, 95s, 100s, 105s, 110s, 115s, 120s.

[0100] Through a large number of experiments, the applicant has also found that when the erosion coefficient γ has different values, there is a corresponding frosting treatment time with higher efficiency and better product performance. If the frosting treatment time deviates from the above-mentioned appropriate time, the glass may not be fully eroded, the glossiness is higher (for example, higher than 90%), the haze is correspondingly lower (for example, lower than 5%), and the anti-glare effect is poor; if the frosting treatment time deviates from the above-mentioned appropriate time, the glass surface may be severely eroded, resulting in a lower transmittance (for example, lower than 85%).

[0101] In some embodiments, in the preparation method, the erosion coefficient γ is calculated based on the mass percentage of the components, and the erosion coefficient γ is (1.5×SiO2+CaO) / ln(Al2O3×100). When the erosion coefficient γ is 0.356-0.390, the frosting treatment time is 120s±5s.

[0102] In some embodiments, in the preparation method, when the erosion coefficient γ is 0.391 to 0.450, the frosting treatment time is 90s±4s.

[0103] In some embodiments, in the preparation method, when the erosion coefficient γ is 0.451-0.519, the frosting treatment time is 60s±3s.

[0104] In the field of glass surface treatment, the process of treating glass with frosting paste, frosting liquid, etc. is generally called frosting process. In this application, only the process of surface treating sodium aluminum silicate glass with frosting liquid is called frosting treatment. The components of frosting liquid referred to in this application are raw materials for preparing frosting liquid. The preparation process of frosting liquid requires mixing and ripening the various components for a period of time to obtain liquid frosting liquid.

[0105] In some embodiments, in the preparation method, the frosting liquid contains, by weight, 6 to 10 parts of ammonium bifluoride, 4 to 6 parts of potassium fluoride, 4 to 6 parts of ammonium sulfate, 5 to 7 parts of potassium sulfate, 2 to 5 parts of hydrochloric acid, 1 to 2 parts of sulfuric acid, and 10 to 15 parts of water.

[0106] In some embodiments, in the preparation method, the frosting liquid contains, by weight, 6 to 8 parts of ammonium bifluoride, 4 to 5 parts of potassium fluoride, 5 to 6 parts of ammonium sulfate, 5 to 6 parts of potassium sulfate, 2 to 3 parts of hydrochloric acid, 1 to 2 parts of sulfuric acid, and 10 to 12 parts of water.

[0107] In some embodiments, in the preparation method, the frosting liquid contains, by weight, 6 parts of ammonium bifluoride, 4 parts of potassium fluoride, 5 parts of ammonium sulfate, 5 parts of potassium sulfate, 2 parts of hydrochloric acid, 1-2 parts of sulfuric acid, and 10 parts of water.

[0108] As mentioned above, the frosting liquid is prepared by mixing the components of the frosting liquid according to a certain proportion and aging them for a period of time to obtain a liquid frosting liquid. The aging time is generally 10 to 30 minutes; the mixing and aging are carried out at room temperature (25°C ± 5).

[0109] The frosting liquid has a simple composition, stable ingredients, does not require heating and stirring, and has little pollution to the environment; the frosting liquid is used for frosting treatment in combination with the pre-etching, pickling and polishing methods of frosting treatment, and has a high surface treatment efficiency for sodium aluminum silicate glass.

[0110] In some embodiments, in the preparation method, the first acid solution containing hydrofluoric acid is prepared from 40 to 60 parts of 15 g / mL hydrofluoric acid and 40 to 60 parts of 6 g / mL sulfuric acid, calculated by weight.

[0111] In some embodiments, in the preparation method, the acid solution not containing hydrofluoric acid is prepared by 40 to 60 parts of 16 g / mL sulfuric acid and 40 to 60 parts of 5 g / mL hydrochloric acid, calculated by weight.

[0112] In some embodiments, in the preparation method, the second acid solution containing hydrofluoric acid is prepared by 40 to 60 parts of 15 g / mL hydrofluoric acid and 40 to 60 parts of 6 g / mL sulfuric acid, calculated by weight.

[0113] In some embodiments, the first acid solution containing hydrofluoric acid and the second acid solution containing hydrofluoric acid have the same preparation method and composition.

[0114] In some embodiments, the first acid solution containing hydrofluoric acid and the second acid solution containing hydrofluoric acid have different preparation methods and compositions.

[0115] The role of pre-etching is to erode the glass surface. On the one hand, it can remove defects such as scratches, and on the other hand, it is conducive to the smooth progress of the frosting process. If the pre-etching time is lower than the appropriate range, the defective layer on the glass surface may not be completely eroded, affecting the subsequent etching process; if the pre-etching time is higher than the appropriate range, the glass may be eroded too much, the final thickness will be lower than the required range, and the mechanical properties of the glass product will also be reduced.

[0116] In some embodiments, in the preparation method, the pre-etching treatment time is 5 to 20 seconds, further can be 7 to 15 seconds, and further can be 9 to 12 seconds.

[0117] The purpose of pickling is to wash away the loose crystals on the glass surface. If the pickling time is lower than the appropriate range, the loose crystals may not be fully washed away, resulting in poor optical performance; if the pickling time is higher than the appropriate range, the crystals that were originally firmly attached to the surface may also be washed away, resulting in poor frosting effect.

[0118] In some embodiments, in the preparation method, the pickling treatment time is 2 to 7 minutes, further can be 3 to 6 minutes, and further can be 4 to 5 minutes.

[0119] The purpose of post-polishing is to reduce the peak-to-valley difference of the uneven surface of the frosted glass by reacting hydrofluoric acid with the surface, and obtain a uniform and fine rough surface. If the post-polishing time is lower than the appropriate range, the unevenness of the glass surface may be too large, and the optical performance may deteriorate; if the post-polishing time is higher than the appropriate range, the glass surface may be too flat, and the anti-glare effect may be lost.

[0120] In some embodiments, in the preparation method, the time of the post-throwing treatment is 7 to 14 minutes, further can be 8 to 13 minutes, and further can be 10 to 12 minutes.

[0121] In some embodiments, in the preparation method, the time of the pre-etching treatment is 5 to 20 seconds, the time of the pickling treatment is 2 to 7 minutes, and the time of the post-polishing treatment is 7 to 14 minutes.

[0122] A third aspect of the present application provides an anti-glare glass prepared by the preparation method described in the second aspect.

[0123] The anti-glare glass has high transmittance and low haze, and also has excellent glossiness, glossiness extreme difference and surface roughness parameters.

[0124] In some embodiments, the surface roughness of the anti-glare glass is ≤0.05μm, and can also be selected from one or two intervals of the following surface roughness: 0.005μm, 0.01μm, 0.02μm, 0.03μm, 0.032μm, 0.035μm, 0.036μm, 0.038μm, 0.039μm, 0.04μm, 0.041μm, 0.042μm, 0.045μm, 0.046μm, 0.047μm, 0.048μm, 0.049μm and 0.05μm, etc.

[0125] A fourth aspect of the present application provides a glass-containing product, including a glass structure, wherein the glass structure is prepared using the anti-glare glass described in the third aspect.

[0126] The fifth aspect of the present application provides an application of the anti-glare glass described in the third aspect or the glass product described in the fourth aspect in the preparation of display screens and curtain walls.

[0127] The anti-glare glass is used in the display field and has good transparency and display effect. It also has good anti-glare performance, which is specifically manifested in high gloss, low haze and small surface roughness.

[0128] In order to make it easier to understand and implement the present invention, the following more specific and detailed embodiments and comparative examples which are easier to implement are provided as references.

[0129] Unless otherwise specified, the raw materials used in the following tests can be purchased from the market. The performance test methods are as follows:

[0130] Test method:

[0131] Transmittance test method: Use ultraviolet spectrophotometer for testing, and the test wavelength range is 380nm~780nm.

[0132] Gloss test method: gloss meter is used to test gloss. The specific method is to use a gloss meter to test.

[0133] The test and calculation method of gloss extreme difference: divide a rectangular sample evenly into nine squares (i.e., two adjacent sides are divided into three equal parts); measure the center point of each nine-square grid three times and take the average value; the difference between the maximum and minimum gloss values ​​of the 9 points is the extreme value.

[0134] Haze testing method: Use a haze meter to test visible light transmittance and haze. The specific method is to use a haze meter to test.

[0135] Surface roughness testing method: Use a roughness meter to test the surface roughness. The specific method is to use a roughness meter to test.

[0136] Anti-glare performance: In this application, the judgment criteria for anti-glare performance are shown in the following table: When the gloss, extreme gloss, transmittance, haze, and surface roughness meet the ranges in the table below, the anti-glare performance of the anti-glare glass is considered to be "good", "qualified" or "poor".

[0137]

[0138] The following are specific embodiments.

[0139] Table 1 Glass composition of Examples 1 to 10

[0140]

[0141] Table 2 Glass properties of Examples 1 to 10

[0142]

[0143] Example 1

[0144] According to the composition of the glass in Table 1, the corresponding batch materials are calculated and weighed based on 1400g of glass liquid. After grinding and mixing evenly, they are placed in a platinum crucible. The platinum crucible is placed in a lifting furnace and heated to 1580℃~1600℃. After keeping warm for 6 hours, the temperature is reduced to 1550℃~1570℃. After keeping warm for another hour, it is poured into a rectangular graphite mold with a size of 200mm×120mm and heated to 500℃~520℃. After hardening, it is transferred to an annealing furnace that has been raised to 680~700℃. After keeping warm for 3 hours, it is cooled to room temperature with the furnace.

[0145] It was cut into sheets of 140 mm × 70 mm × 0.7 mm, double-sided ground and polished, and CNC processed.

[0146] then,

[0147] A sodium aluminum silicate glass is placed as a glass original sheet in a first acid solution containing hydrofluoric acid (15% hydrofluoric acid and 6% dilute sulfuric acid in a weight / volume ratio of 1:1) for pre-etching, and then washed and dried after the pre-etching;

[0148] The crude product after the pre-etching treatment is placed in a frosting solution for frosting treatment for 120 seconds;

[0149] The frosted crude product is placed in an acid solution without hydrofluoric acid (6% dilute sulfuric acid and 5% dilute hydrochloric acid in a weight / volume ratio of 1:1) for pickling treatment, and then post-polished with a second acid solution containing hydrofluoric acid (15% hydrofluoric acid and 6% dilute sulfuric acid in a weight / volume ratio of 1:1), washed and dried.

[0150] The haze meter was used to test the visible light transmittance and haze, the gloss meter was used to test the gloss, and the roughness meter was used to test the surface roughness. The performance parameters obtained are as follows:

[0151] The transmittance is 90.53%, the glossiness is 85.8%, the glossiness range is 5%, the haze is 8.5%, and the surface roughness is 0.042 μm.

[0152] Example 2

[0153] The glass raw sheet was prepared according to the glass composition in Table 1, and cut, double-sided polished, and CNC processed using the same method.

[0154] The preparation method of the anti-glare glass of Example 2 is substantially the same as that of Example 1.

[0155] The same test method is used for testing, and the performance parameters obtained are as follows:

[0156] The transmittance was 91.2%, the glossiness was 88.7%, the glossiness range was 4.5%, the haze was 9.1%, and the surface roughness was 0.05 μm.

[0157] Example 3

[0158] The glass raw sheet was prepared according to the glass composition in Table 1, and cut, double-sided polished, and CNC processed using the same method.

[0159] The method for preparing the anti-glare glass of Example 3 is substantially the same as that of Example 1, except that the frosting treatment time is 60 seconds.

[0160] The same test method is used for testing, and the performance parameters obtained are as follows:

[0161] The transmittance is 88.95%, the glossiness is 75.3%, the glossiness range is 4.6%, the haze is 12.5%, and the surface roughness is 0.036 μm.

[0162] Example 4

[0163] The glass raw sheet was prepared according to the glass composition in Table 1, and cut, double-sided polished, and CNC processed using the same method.

[0164] The preparation method of the anti-glare glass of Example 4 is substantially the same as that of Example 1, except that the frosting treatment time is 90 seconds.

[0165] The same test method is used for testing, and the performance parameters obtained are as follows:

[0166] The transmittance is 89.97%, the glossiness is 79.5%, the glossiness difference is 3.8%, the haze is 10.4%, and the surface roughness is 0.045 μm.

[0167] Example 5

[0168] The glass raw sheet was prepared according to the glass composition in Table 1, and cut, double-sided polished, and CNC processed using the same method.

[0169] The preparation method of the anti-glare glass of Example 5 is substantially the same as that of Example 1, except that the frosting treatment time is 60 seconds.

[0170] The same test method is used for testing, and the performance parameters obtained are as follows:

[0171] The transmittance was 88.5%, the glossiness was 84.3%, the glossiness range was 3.8%, the haze was 11.8%, and the surface roughness was 0.041 μm.

[0172] Example 6

[0173] The glass raw sheet was prepared according to the glass composition in Table 1, and cut, double-sided polished, and CNC processed using the same method.

[0174] The preparation method of the anti-glare glass of Example 6 is substantially the same as that of Example 1, except that the frosting treatment time is 90 seconds.

[0175] The same test method is used for testing, and the performance parameters obtained are as follows:

[0176] The transmittance was 90.12%, the glossiness was 81.2%, the glossiness range was 2.9%, the haze was 10.7%, and the surface roughness was 0.039 μm.

[0177] Example 7

[0178] The glass raw sheet was prepared according to the glass composition in Table 1, and cut, double-sided polished, and CNC processed using the same method.

[0179] The preparation method of the anti-glare glass of Example 7 is basically the same as that of Example 1.

[0180] The same test method is used for testing, and the performance parameters obtained are as follows:

[0181] The transmittance is 90.76%, the glossiness is 77.8%, the glossiness range is 3.5%, the haze is 9.9%, and the surface roughness is 0.032 μm.

[0182] Example 8

[0183] The glass raw sheet was prepared according to the glass composition in Table 1, and cut, double-sided polished, and CNC processed using the same method.

[0184] The preparation method of the anti-glare glass of Example 8 is substantially the same as that of Example 1, except that the frosting treatment time is 90 seconds.

[0185] The same test method is used for testing, and the performance parameters obtained are as follows:

[0186] The transmittance is 89.52%, the glossiness is 76.2%, the glossiness difference is 4%, the haze is 12%, and the surface roughness is 0.038 μm.

[0187] Example 9

[0188] The glass raw sheet was prepared according to the glass composition in Table 1, and cut, double-sided polished, and CNC processed using the same method.

[0189] The preparation method of the anti-glare glass of Example 9 is substantially the same as that of Example 1, except that the frosting treatment time is 90 seconds.

[0190] The same test method is used for testing, and the performance parameters obtained are as follows:

[0191] The transmittance is 88.96%, the glossiness is 77.1%, the glossiness difference is 3.7%, the haze is 11.6%, and the surface roughness is 0.046 μm.

[0192] Example 10

[0193] The glass raw sheet was prepared according to the glass composition in Table 1, and cut, double-sided polished, and CNC processed using the same method.

[0194] The preparation method of the anti-glare glass of Example 10 is basically the same as that of Example 1.

[0195] The same test method is used for testing, and the performance parameters obtained are as follows:

[0196] The transmittance is 90.41%, the glossiness is 86.5%, the glossiness range is 4.3%, the haze is 9.3%, and the surface roughness is 0.042 μm.

[0197] It can be seen that the transmittance of Examples 1 to 10 is higher than 88%, which can be used for display screens; the surface roughness is 0.05 μm or less, indicating that the frosting uniformity is good. At the same time, the haze range is 8.5% to 12.5%, and the gloss range is 75.3% to 86.5%. While maintaining high transmittance, the glass of the present application can select different anti-glare effects to adapt to different scenes.

[0198] Table 3 Glass compositions of Comparative Examples 1 to 7

[0199]

[0200] Table 4 Glass properties of Comparative Examples 1 to 6

[0201]

[0202] Comparative Example 1

[0203] The glass original sheet was prepared according to the glass composition in Table 3, and cut, double-sided polished, and CNC processed using the same method.

[0204] The preparation method of the anti-glare glass of Comparative Example 1 is substantially the same as that of Example 1, except that the frosting treatment time is 90 seconds.

[0205] The same test method is used for testing, and the performance parameters obtained are as follows:

[0206] The transmittance is 88.45%, the glossiness is 76.6%, the glossiness extreme difference is 10.8% greater than 10%, the haze is 14.5% greater than 13%, and the surface roughness is 0.048μm.

[0207] The possible reasons are that the value of (SiO2+Al2O3)-(CaO+MgO) is 65.3, which is lower than 66; the value of (Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO) is 144, which is higher than 115, causing the surface tension of the glass to exceed the appropriate range, thereby aggravating the instability of the frosting process, and adversely affecting the gloss of the anti-glare glass; the erosion coefficient γ=0.01×(1.5SiO2+CaO) / ln(Al2O3) is 0.39, and the actual frosting treatment time is 90s. Although γ is in the range of 0.3 to 0.6, it deviates from the preferred frosting treatment time of 120s±5s, resulting in poor uniformity during the frosting treatment process, extremely poor optical quality and deteriorated haze performance.

[0208] Comparative Example 2

[0209] The glass original sheet was prepared according to the glass composition in Table 3, and cut, double-sided polished, and CNC processed using the same method.

[0210] The preparation method of the anti-glare glass of Comparative Example 2 is substantially the same as that of Example 1, except that the frosting treatment time is 90 seconds.

[0211] The same test method is used for testing, and the performance parameters obtained are as follows:

[0212] The transmittance is 90.12%, the glossiness is 83.5%, the glossiness extreme difference is 11.5% greater than 10%, the haze is 6.7% less than 7%, and the surface roughness is 0.039μm.

[0213] The reason may be that the value of (SiO2+Al2O3)-(CaO+MgO) is 75.7, which is higher than 74. During the etching process, more reaction products with lower solubility are obtained, resulting in the inability to further erode the covered area, aggravating the uneven degree of erosion, and making the glass surface matte, resulting in extremely poor gloss and deteriorated haze performance.

[0214] Comparative Example 3

[0215] The glass original sheet was prepared according to the glass composition in Table 3, and cut, double-sided polished, and CNC processed using the same method.

[0216] The preparation method of the anti-glare glass of Comparative Example 3 is substantially the same as that of Example 1, except that the frosting treatment time is 60 seconds.

[0217] The same test method is used for testing, and the performance parameters obtained are as follows:

[0218] The transmittance is 84.81% less than 85%, the glossiness is 82.8%, the glossiness extreme difference is 4.8%, the haze is 9.2%, and the surface roughness is 0.071μm greater than 0.5μm.

[0219] The possible reasons are that the value of (Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO) is 131.9, which is higher than 115, causing the surface tension of the glass to exceed the appropriate range, thereby aggravating the instability of the frosting process, and adversely affecting the gloss of the anti-glare glass; the erosion coefficient γ=0.01×(1.5SiO2+CaO) / ln(Al2O3) is 0.37, and the actual frosting treatment time is 60s. Although γ is in the range of 0.3-0.6, it deviates from the preferred frosting treatment time of 120s±5s, resulting in a decrease in its transmittance and deterioration of surface roughness.

[0220] Comparative Example 4

[0221] The glass original sheet was prepared according to the glass composition in Table 3, and cut, double-sided polished, and CNC processed using the same method.

[0222] The preparation method of the anti-glare glass of Comparative Example 4 is substantially the same as that of Example 1, except that the frosting treatment time is 60 seconds.

[0223] The same test method is used for testing, and the performance parameters obtained are as follows:

[0224] The transmittance is 83.27% less than 85%, the glossiness is 86.5%, the glossiness extreme difference is 4.2%, the haze is 10.4%, and the surface roughness is 0.067μm greater than 0.5μm.

[0225] The reason for the performance degradation may be that the value of (Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO) is 149.4, which is significantly higher than 115, causing the surface tension of the glass to exceed the appropriate range, thereby aggravating the instability of the frosting process, and adversely affecting the gloss of the anti-glare glass; the erosion coefficient γ=0.01×(1.5SiO2+CaO) / ln(Al2O3) is 0.45, and the actual frosting treatment time is 60s. Although γ is in the range of 0.3~0.6, it deviates from the preferred frosting treatment time of 90s±4s, which also leads to the deterioration of its transmittance and surface roughness.

[0226] Comparative Example 5

[0227] The glass original sheet was prepared according to the glass composition in Table 3, and cut, double-sided polished, and CNC processed using the same method.

[0228] The preparation method of the anti-glare glass of Comparative Example 5 is substantially the same as that of Example 1.

[0229] The same test method is used for testing, and the performance parameters obtained are as follows:

[0230] The transmittance is 82.53% less than 85%, the glossiness is 72.7% less than 75%, the glossiness extreme difference is 3.9%, the haze is 15.3% greater than 13%, and the surface roughness is 0.044μm.

[0231] The reason for the deterioration of the performance of the glass product in this comparative example may be that the value of (Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO) is 128.6, which is significantly higher than that of the conventional frosting process, causing the surface tension of the glass to exceed the appropriate range, thereby aggravating the instability of the frosting process and adversely affecting the glossiness of the anti-glare glass; the value of the erosion coefficient γ=0.01×(1.5SiO2+CaO) / ln(Al2O3) is 128.6, and the actual frosting treatment time is 120s. Although γ is within the range of 0.3 to 0.6, it deviates from the preferred frosting treatment time of 60s±3s, resulting in the deterioration of the transmittance, glossiness and haze performance.

[0232] Comparative Example 6

[0233] The glass original sheet was prepared according to the glass composition in Table 3, and cut, double-sided polished, and CNC processed using the same method.

[0234] The preparation method of the anti-glare glass of Comparative Example 6 is substantially the same as that of Example 1, except that the frosting treatment time is 60 seconds.

[0235] The same test method is used for testing, and the performance parameters obtained are as follows:

[0236] The transmittance was 91.01%, the glossiness was 91.3%, the glossiness range was 4%, the haze was 5.8%, and the surface roughness was 0.047 μm.

[0237] The reason for the deterioration of the performance of the glass product may be the erosion coefficient

[0238] The value of γ=0.01×(1.5SiO2+CaO) / ln(Al2O3) is 0.36, and the actual frosting treatment time is 60s. Although γ is in the range of 0.3 to 0.6, it deviates from the preferred frosting treatment time of 120s±5s. The long frosting treatment time causes the crystal precipitates to be continuously deposited on the surface of the glass that is less corroded, which in turn causes uneven deposition of the precipitates, which is manifested as the deterioration of the gloss and haze parameters of the glass product.

[0239] Comparative Example 7

[0240] The glass original sheet was prepared according to the glass composition in Table 3, and cut, double-sided polished, and CNC processed using the same method.

[0241] The composition of Comparative Example 7 except K2O, the value of (SiO2+Al2O3)-(CaO+MgO), the value of (Na2O+K2O)×(SiO2 / Al2O3-CaO / MgO), and the value of the corrosion coefficient γ are all within the required range of the present application, and the K2O content is 0%.

[0242] The preparation method of the anti-glare glass of Comparative Example 7 is substantially the same as that of Example 1, except that the frosting treatment time is 1.5 min.

[0243] The same test method is used for testing, and the performance parameters obtained are as follows:

[0244] The transmittance is 90.87%, the glossiness is 95%, the glossiness extreme difference is 2.5%, the haze is 4.5% less than 7%, and the surface roughness is 0.074μm greater than 0.05μm. This is because the absence of K2O leads to excessively high erosion performance and reduced erosion efficiency, which is specifically manifested in high glossiness and low haze. In addition, due to insufficient erosion, it is still uneven erosion, so the surface is also rough, resulting in a decrease in anti-glare effect.

[0245] In addition, through experiments, the inventors also found that when sodium aluminum silicate glass does not contain MgO, it is impossible to fully utilize the property of MgO itself to reduce corrosion resistance while increasing infringement resistance by enhancing the mixed alkali effect. It is not easy to fine-tune the corrosion resistance to obtain glass with moderate performance, and it is difficult to control the etching process.

[0246] Changes in process conditions during frosting treatment will also have a significant impact on the optical properties of glass: when the pre-etching in frosting treatment is omitted, the erosion efficiency is reduced under the condition that other conditions are the same, which will lead to lower haze and increased surface roughness overall; when the acid pickling in frosting treatment is omitted, other conditions are the same, more crystals are attached to the glass surface, blocking optics and causing a significant decrease in transmittance; when the post-polishing in frosting treatment is omitted, other conditions are the same, the surface roughness increases and the glossiness is significantly reduced because the unevenness of the glass surface is not treated.

[0247] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0248] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A method for preparing anti-glare glass, characterized in that: The following steps are involved: The sodium aluminum silicate glass is placed as a glass original sheet in a first acid solution containing hydrofluoric acid for pre-etching, and then washed and dried after the pre-etching; The crude product after pre-etching treatment is placed in a frosting solution for frosting treatment for 60s to 120s; The frosted crude product is placed in an acid solution without hydrofluoric acid for pickling, and then subjected to post-polishing treatment in a second acid solution containing hydrofluoric acid, and then washed and dried; Wherein, the sodium aluminum silicate glass, according to mass percentage, the preparation raw materials include the following components: 58% to 70% SiO2, 8% to 13% Al2O3, 13% to 18% Na2O, 2.5% to 5.5% K2O, 2% to 5.5% MgO, 0% to 3% CaO, 0% to 1.5% ZrO2, and 0% to 1.5% B2O3; Among them, the mass percentage of the components is used for calculation, and the following formula is satisfied: 66%≤(SiO2+Al2O3)-(CaO+MgO)≤75%, 89.8%≤(Na2O+K2O)× (SiO2 / Al2O3-CaO / MgO) ≤112.4%; The erosion coefficient γ is calculated based on the mass percentage of the components, which is (1.5×SiO2+CaO) / ln(Al2O3×100), and the range of γ is 0.356~0.519; When the erosion coefficient γ is 0.356-0.39, the frosting treatment time is 120s ±5s; When the erosion coefficient γ is 0.391-0.45, the frosting treatment time is 90s±4s; When the erosion coefficient γ is 0.451-0.519, the frosting treatment time is 60s±3s.

2. The preparation method according to claim 1, characterized in that: The mass percentage of the components is used for calculation and meets the following characteristics: 68.2%≤(SiO2+Al2O3)-(CaO+MgO)≤74%.

3. The preparation method according to claim 1, characterized in that: In terms of weight, the frosting liquid contains 6-10 parts of ammonium bifluoride, 4-6 parts of potassium fluoride, 4-6 parts of ammonium sulfate, 5-7 parts of potassium sulfate, 2-5 parts of hydrochloric acid, 1-2 parts of sulfuric acid, and 10-15 parts of water.

4. The preparation method according to claim 1, characterized in that: The first acid solution containing hydrofluoric acid is prepared by 40 to 60 parts of 15 g / mL hydrofluoric acid and 40 to 60 parts of 6 g / mL sulfuric acid in parts by mass.

5. The preparation method according to claim 1, characterized in that The acid solution not containing hydrofluoric acid is prepared by 40 to 60 parts of 16 g / mL sulfuric acid and 40 to 60 parts of 5 g / mL hydrochloric acid in parts by mass.

6. The preparation method according to claim 1, characterized in that The second acid solution containing hydrofluoric acid is prepared by 40 to 60 parts of 15 g / mL hydrofluoric acid and 40 to 60 parts of 6 g / mL sulfuric acid in parts by mass.

7. The preparation method according to any one of claims 1 to 6, characterized in that The time of the pre-etching treatment is 5 to 20 seconds.

8. The preparation method according to any one of claims 1 to 6, characterized in that: The pickling treatment time is 2 to 7 minutes.

9. The preparation method according to any one of claims 1 to 6, characterized in that: The time of the post-throwing treatment is 7 to 14 minutes. 10.An anti-glare glass, characterized in that: The method is prepared by any one of claims 1 to 9.

11. A glass-containing product, characterized in that It comprises a glass structure, and the glass structure is prepared by using the anti-glare glass according to claim 10.

12. Use of the anti-glare glass according to claim 10 or the glass-containing product according to claim 11 in the preparation of display screens and curtain walls.

Citation Information

Patent Citations

  • Cover glass and method for producing cover glass

    CN102557464A

  • Process for producing anti-glare glass by using high-boron silicon and high-aluminium silicon glasses

    CN102887647A